PRODUKSI DAN KARAKTERISASI ENZIM KITINASE DARI BAKTERI KITINOLITIK ASAL KERANG Anadara granosa - Nur Haedar; Fahruddin Fahruddin; Wilda Aryanti; Hasnah Natsir (Universitas Hasanuddin, 2017)
This research aims to investigate the maximal generation time and the characterization of chitinase enzyme of Chitinolytic bacteria from Anadara granosa shell in various pH, temperature and substrate concentration. The result of the maximal time of Chitinolytic bacteria was showed at 120 hours. The result of Chitinolytic bacteria characteristic in various pH shows that the highest activity of chitinase is on pH 6 and in various temperature shows that the highest activity at 350C while in various substrate concentration shows that the highest activity value of chitinase is on substrate concentration 0.5%. Keywords: Characterization, Chitinolytics Bacteria, Chitinase Enzyme